2017
DOI: 10.1177/1179299x17710944
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fascin-1 in Relation to Gleason Risk Classification and Nuclear ETS-Related Gene Status of Human Prostate Carcinomas: An Immunohistochemical Study of Clinically Annotated Tumours From the Wales Cancer Bank

Abstract: Although prostate-specific antigen (PSA) testing can identify early-stage prostate cancers, additional biomarkers are needed for risk stratification. In one study, high levels of the actin-bundling protein, fascin-1, were correlated with lethal-phase, hormone-refractory prostate cancer. Analyses of independent samples are needed to establish the value of fascin-1 as a possible biomarker. We examined fascin-1 by immunohistochemistry in tumour specimens from the Wales Cancer Bank in comparison with nuclear-locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…TMA demonstrated that the general expression of CEMIP in PCa tissue was substantially higher compared with that in their pericarcinous counterparts. Surprisingly, in the present work, the expression of CEMIP did not seem to be positively statistically correlated with GS, and some reports also observed that the current GS system might occasionally fail to represent-as an indicator-PCa progression and expression of certain oncogenes (31)(32)(33). Of note, CEMIP was indeed more intensively expressed in intermediate-and high-risk patients compared with their low-risk counterparts (data not shown).…”
Section: Discussioncontrasting
confidence: 79%
“…TMA demonstrated that the general expression of CEMIP in PCa tissue was substantially higher compared with that in their pericarcinous counterparts. Surprisingly, in the present work, the expression of CEMIP did not seem to be positively statistically correlated with GS, and some reports also observed that the current GS system might occasionally fail to represent-as an indicator-PCa progression and expression of certain oncogenes (31)(32)(33). Of note, CEMIP was indeed more intensively expressed in intermediate-and high-risk patients compared with their low-risk counterparts (data not shown).…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, it was recently demonstrated that targeted inhibition of FSCN1 could interfere with tumor invasion and metastatic potential [ 58 , 59 ]. The analysis of FSCN1 using immunohistochemistry in prostate carcinoma glands found that only 8% of PCa had more than 10% FSCN1 positivity; FSCN1 expression, however, did not correlate with Gleason score, tumor stage, serum PSA levels or biochemical relapse following surgery [ 43 ]. The analysis of FSCN1 mRNA expression in different PCa datasets showed a quite limited diagnostic role of FSCN1, although increased in metastatic disease [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported in recent immunohistochemical analyses of FSCN1 expression in PCa tissue, no correlation was found with Gleason score, tumor stage and PSA values. However, the analysis of FSCN1 using immunohistochemistry in prostate carcinoma glands (several hundred prostate specimens of all Gleason risk scores) found that only 8% of the tumors had more than 10% FSCN1 positivity, and the stromal tumor cells, and stromal levels of FSCN1 were highly increased in high Gleason score [ 43 , 44 ]. We have proposed two objectives to study FSCN1 in PCa.…”
Section: Fscn1 In Prostate Cancermentioning
confidence: 99%
“…97,98 Limited and hormone-refractory PCas show a significant upregulation of fascin-1 expression than that in benign prostate tissue. 6,68,69,99 In addition, a follow-up of patients undergoing radical prostatectomy has shown high fascin-1 expression to be related to an increased rate of PSA recurrence. 68 High fascin-1 expression is related to Gleason score and bone metastases, 69 thus confirming its role in PCa progression.…”
Section: Fascin-1 and Pcamentioning
confidence: 99%
“…However, PSA cannot accurately distinguish between inert tumors and aggressive disease. 6 Therefore, new clinical prognostic PCa biomarkers are needed to better differentiate inert prostate tumors from PCa. 7,8 Fascin-1 is a 55 kDa cytoskeleton protein, which binds to F-actin and participates in cell division, cell migration, and intercellular interactions.…”
Section: Introductionmentioning
confidence: 99%